Noninvasive discrimination of low and high-risk pancreatic intraductal papillary mucinous neoplasms - Roth, Susanne; Bose, Promita; Alhamdani, Mohamed Saiel Saeed; Mustafa, Shakhawan A.; Tjaden, Christin; Zamzow, Katharina Morgane; Hinz, Ulf; Michalski, Christoph; Neoptolemos, John P.; Hoheisel, Jörg D.; Büchler, Markus W.; Hackert, Thilo (Annals of surgery, 2020)
Objective: - To propose a noninvasive diagnostic approach, which allows reliable distinction between low- and high-risk pancreatic intraductal papillary mucinous neoplasms (IPMNs). - Background: - IPMNs are identifiable precursor lesions of pancreatic cancer, of which surgical resection is warranted prior to the development of invasive carcinoma, but low-grade IPMNs should not be unnecessarily resected. However, diagnostic tools that preoperatively enable accurate risk stratification of IPMNs are missing. - Methods: - This single-center, retrospective cohort study included 56 patients who underwent surgical resection for IPMN including 18 low-risk (low-grade) and 38 high-risk (high-grade/invasive carcinoma) IPMNs, from whom clinical features and serum samples were prospectively obtained. An antibody microarray platform was used to analyze the serum proteome. Based on serum markers and selected clinical characteristics support vector machine models were constructed to predict the risk of IPMN malignancy. - Results: - A serum protein signature discriminating low- and high-risk IPMN patients was identified. Combinations of established clinical features and the newly identified serum biomarkers correctly distinguished low- and high-risk IPMNs in 93% on 1000-fold cross-validation. - Conclusions: - This study highlights the synergistic predictive value of combining a novel serum protein signature with conventional clinical characteristics to risk-stratify IPMN patients. If these findings are supported by larger validation studies, they might enable more rational decision-making in clinical management of IPMN patients in conjunction with clinical guidelines.